A systematic review of exploratory factor analysis packages in R software - Priyalatha a/p Govindasamy, Nor Junainah binti Mohd Isa, Nor Firdous Mohamed, Amelia binti Mohd Noor (Tanjung Malim, 2024)
A systematic review of exploratory factor analysis packages in R software by Priyalatha a/p Govindasamy, Nor Junainah binti Mohd Isa, Nor Firdous Mohamed, Amelia binti Mohd Noor